New insights into the proteomic characterization of the coral snake Micrurus pyrrhocryptus venom. (October 2018) - Olamendi-Portugal, Timoteo; Batista, César V.F.; Pedraza-Escalona, Martha; Restano-Cassulini, Rita; Zamudio, Fernando Z.; Benard-Valle, Melisa; de Roodt, Adolfo Rafael; Possani, Lourival D.
Abstract: A proteomic analysis of the soluble venom of the coral snake Micrurus pyrrhocryptus is reported in this work. The whole soluble venom was separated by RP-HPLC and the molecular weights of its components (over 100) were determined by mass spectrometry. Three main sets of components were identified, corresponding to peptides with molecular masses from 5 to 8 kDa, proteins from 12 to 16 kDa and proteins from 20 to 30 kDa. Two components were fully sequenced: one α-neurotoxic peptide of 7210 Da with slight blocking activity of the nicotinic acetylcholine receptor (nAChR) and a phospholipase A2 (PLA2 ) with molecular weight 13517 Da and no effect on the nAChR. PLA2 activity was evaluated for all RP-HPLC components. In addition, N-terminal sequence was obtained for eleven components using Edman degradation. Among these, three were similar to known PLA2 's, six to three-finger toxins (3FTx) and one to Kunitz-type serine protease inhibitors. Two-dimensional gel electrophoresis of the venom allowed the separation of about thirty spots with components of molecular weights from 25 to 70 kDa. Seventeen spots were recovered from the gel, digested with trypsin and the corresponding peptides (85) were sequenced by MS/MS allowing identification of amino acid sequences with similarities to snake venom metalloproteases (SVMP), PLA2 's, L-amino acid oxidases (LAAO), acetylcholinesterases (AChE) and serine proteases (SP). In addition, LC-MS analysis of peptides obtained from tryptic digestion of whole soluble venom allowed the identification of 695 peptides, whose amino acid sequence could correspond to at least 355 components found in other snake venoms, where C-type lectins, vespryns, zinc finger proteins, and waprins were found, among others. These results show the complexity of the venom and provide important knowledge for future work on identification and activity determination of venom components from this coral snake. Graphical abstract: Highlights: Components of this coral snake were separated by HPLC and two-dimensional gel electrophoresis. A complete finger-printing of soluble venom was obtained by mass spectrometry after HPLC separation. Edman degradation and mass spectrometry analyses allowed the identification of 355 distinct components. Three main types of components were identified: three-finger peptides, phospholipases and hydrolytic enzymes. Neurotoxic three-finger peptides predominates in this venom, followed by phospholipases A2 .